Perbandingan program latihan pada klub sepak bola kabupaten kolaka utara dan kota palopo - Patandean, Rei; Jalil, Rasyidah; Saman, Saman; Kahar, Irsan (Universitas Hamzanwadi, 2023)
The training program is a way to carry out training effectively and efficiently so that it is hoped that it can achieve the targets that have been set. The implementation of this research was carried out in two places, this study aimed to find out the training program for the southeast and palopo clubs. Based on the results of interviews from the two clubs, it can be stated that the Palopo club is superior to the Southeastern club. The method in this study was descriptive qualitative by distributing co-signers or conducting direct interviews. The subjects of this study were football athletes and coaches. Based on the results of the study, it can be concluded that the training program between the two clubs has differences where the Palopo club training program is superior and effective in achieving maximum results when competing.